Clinical Features, Genotype-Phenotype Correlations and Treatment Outcomes in Children and Adolescents with Multiple Endocrine Neoplasia Type 1: An International Cohort Study - Shariq, Omair (Journal of the Nuffield Department of Surgical Sciences, 2021)
Omair A. Shariq1,2, Kate E. Lines3, Katherine A. English3, Bahram Jafar-Mohammadi3, Philippa Prentrice3, Ruth Casey5, Benjamin G. Challis5, Andreas Selberherr6, Fiona J. Ryan3, Ultan Healy3, Tom Kurzawinski7, Mehul T Dattani7, Irina Bancos8, Duncan Richards9, Benzon M. Dy2, Melanie L. Lyden2, William F. Young, Jr.8, Travis J. McKenzie2, Rajesh V. Thakker3 1Nuffield Department of Surgical Sciences, University of Oxford, UK 2Department of Surgery, Mayo Clinic, Rochester, MN 3Oxford Centre for Diabetes, Endocrinology and Metabolism, University of Oxford, UK 4Department of Paediatric Endocrinology, Great Ormond Street Hospital for Children, London, UK 5Department of Endocrinology, Cambridge University Hospital NHS Foundation Trust, Cambridge, UK. 6Department of Surgery, Medical University of Vienna, Vienna, Austria. 7Centre for Endocrine Surgery, Great Ormond Street Hospital for Children, London, UK 8Division of Endocrinology, Diabetes, Metabolism, and Nutrition, Mayo Clinic, Rochester, MN 9Oxford Clinical Trials Research Unit, Botnar Research Centre, Oxford, UK Background: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant disorder characterised by parathyroid, pituitary and duodenopancreatic neuroendocrine tumours (DP-NETs). Knowledge regarding manifestations and outcomes is largely derived from adult cohorts. Thus, we investigated the occurrence and treatment of MEN1 manifestations in children and adolescents, and also explored potential genotype-phenotype correlations. Methods Eighty MEN1 patients who underwent childhood/adolescent tumour surveillance at 5 international referral centres were included. Fisher’s exact, Wilcoxon rank-sum and Kaplan-Meier tests were used to compare proportions, continuous variables and recurrence-free survival, respectively. Results Fifty-six patients (70%) developed an MEN1 manifestation before 19 years, at a median age of 14 years (range: 6-18 years). Primary hyperparathyroidism occurred in 46/56 patients (82.1%), 33 (72%) of whom underwent parathyroidectomy. Less-than-subtotal (<3-gland) parathyroidectomy resulted in worse recurrence/persistence-free survival vs subtotal (3-3.5-gland) or total (4-gland) parathyroidectomy (median 27 months vs not reached; P=0.005). Twenty-one patients (37.5%) developed DP-NETs (non-functioning [n=15], insulinomas [n=8], and gastrinoma [n=1]), 12 (57.1%) underwent surgery and 3 (14.3%) had metastases (hepatic [n=2] and lymph node [n=1]). Compared to patients without DP-NETs, those with DP-NETs at <19 years were more likely to harbour MEN1 mutations disrupting the menin-JunD interaction domain (80% vs 51.9%; P=0.0459). Pituitary tumours developed in 18/56 patients (32%) and were mostly dopamine agonist-responsive prolactinomas. Conclusions Morbidity from MEN1 manifestations occurs during childhood and adolescence in 70% of patients. Less-than-subtotal parathyroidectomy leads to high failure rates. DP-NETs are the second most common manifestation in this age group and may be more frequent in patients with mutations that disrupt menin-JunD binding.